Concurrent left ventricular pseudoaneurysm and ventricular septal rupture complicating an inferior myocardial infarction: A case report - Yosra Abdulahad Turkistani, MD; Sara Hajij Al-Harbi, MD; Fatma Adel Aboul-Enein, MD (Radiology Case Reports)
The mechanical complications postmyocardial infarction are individually uncommon but potentially life-threatening. The simultaneous occurrence of more than one complication in a single patient is rare and presents a significant diagnostic and therapeutic challenge. We present a case of concurrent left ventricular pseudoaneurysm and ventricular septal rupture post a late presentation, inferoposterior myocardial infarction. This case highlights the importance of multimodality imaging in correctly diagnosing and properly guiding the management plan for these complications, which can dramatically impact patient outcomes.